THE RECOVERY OF DEPRESSIVE PATIENTS: A REVIEW ON THE ROLES OF SOCIAL WORKER - Idris, Afifah (International Journal of Psychosocial Rehabilitation, 2020)
Since the early years of the profession, social work has had a commitment to work with people who have psychiatric disabilities by offering psychosocial interventions. This review acknowledged the critical roles of social worker in the journey of recovering for depressive patients, apart from the role of other mental health professionals. Psychosocial intervention is like two sides of the same coin. A dual partnership between social worker with other mental health professionals is vital to patients’ recovery. However, the role of social workers in mental health setting has been unnoticed. In most part of the countries, patients and communities did not realize the role of social worker, particularly psychiatric social worker, and tended to seek for medical treatment only. Thus, to achieve a successful recovery, more programs related to the psychiatric social worker should be implemented. The main goal of a psychiatric social worker is to stabilize and support people experiencing psychological distress or behavioural issues that are threatening their own and other’s safety and well-being. As the depressive patients are expecting social worker to recognize their difficulties before working together to resolve their conditions, the curriculum of social worker should be improved. The social worker must be able to have the skills in recognizing mental illness issues while working together in a collaborative care. The patient-survivor recovery movement is closely aligned with those of the profession, and that the movement offers social workers a more promising perspective from which to practice.